The Role of the Picture and Picture Method in Developing Students' Creative Thinking Skills - Alberth Supriyanto Manurung; Abdul Halim (Proceeding of the International Conference on Mathematical Sciences, Natural Sciences, and Computing, 2024)
This ponder points to decide the part of the advancement and application of the Picture and Picture Strategy in creating students' Inventive considering abilities in numerical story issues. The consider was conducted within the odd semester of 2023/2024 with 27 Rudimentary School Instruction understudies in semester V as inquire about subjects. The study was conducted employing a subjective investigation strategy with information collection through perception, interviews and documentation. The Picture and Picture Strategy is connected through learning stages, to be specific preparing understudies to utilize different concepts, standards and aptitudes that they have learned to illuminate the numerical story issues they confront. The comes about of the ponder appear that the Picture and Picture Strategy has an affect on the advancement of Imaginative considering aptitudes, since the comes about of inquire about perceptions on Imaginative considering abilities deliver the capacity to recognize, assess, and resolve story challenges and reason reasonably and morally and be able to draw conclusions. The Picture and Picture Strategy gives understudies with the opportunity to apply learning based on fathoming scientific story issues, giving understudies with the opportunity to create Imaginative considering aptitudes.